2015
DOI: 10.5755/j01.ms.21.2.5767
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bonded Seams upon Spatial Behaviour of Knitted Materials Systems

Abstract: Spatial behaviour of knitted materials with bonded seams under biaxial tensile loading is analysed in this work. The objects of the research were plain jersey and rib 1×1 polyester knitted materials with elastane (93 % PES, 7 % EL). Two thermoplastic polyurethane (PU) films different in thickness (75 μm and 150 μm) were used. For each sample of knitted material and thermoplastic film five types of samples with bonded seams (10 mm in length) were prepared by changing the orientation of knitted materials pieces,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…The lengthwise textile specimens were chosen by taking into account the construction instructions commonly being applied in the clothing industry which consider that clothing pieces should be placed warp/wale direction during their cutting from textile materials. Even if one of the previous publications [3] states, that the orientation of knitted materials pieces in bonded seams does not have any significant effect, whereas the other research study [17] reveals that the fabric orientation in the bond makes significant influence on the peeling strength of the lengthwise specimens bonded at both 150 ℃ and 160 ℃ temperatures. Additionally, based on the published research works it may be concluded that, the selected bonding temperature (150 ℃) does not exceed the glass transition temperature (Tg = 226 °C) of polyester fibres refereed in the researches had been published by other scientist (https://us.setaram.com), previously.…”
Section: Bond Peeling Strength Testing Methodologymentioning
confidence: 88%
See 1 more Smart Citation
“…The lengthwise textile specimens were chosen by taking into account the construction instructions commonly being applied in the clothing industry which consider that clothing pieces should be placed warp/wale direction during their cutting from textile materials. Even if one of the previous publications [3] states, that the orientation of knitted materials pieces in bonded seams does not have any significant effect, whereas the other research study [17] reveals that the fabric orientation in the bond makes significant influence on the peeling strength of the lengthwise specimens bonded at both 150 ℃ and 160 ℃ temperatures. Additionally, based on the published research works it may be concluded that, the selected bonding temperature (150 ℃) does not exceed the glass transition temperature (Tg = 226 °C) of polyester fibres refereed in the researches had been published by other scientist (https://us.setaram.com), previously.…”
Section: Bond Peeling Strength Testing Methodologymentioning
confidence: 88%
“…The strong bond, which usually is even stronger than sewn seam, is formed after cooling [2,9]. Bond quality depends on the materials anisotropy, tensile characteristics of thermoplastic films [3], bonding parameters, textile bearing surface and structure mobility [2,3,14] as well as on bond peeling velocity [15].…”
Section: Introduction mentioning
confidence: 99%
“…Our previous investigation has shown that the behaviour of knitted materials bonded seams under biaxial punching before and after cyclical fatigue punching are mostly determined by the thickness of thermoplastic film, but not effected by the orientation of knitted materials strips in bonded seams [14]. The aim of this investigation was to determine the effect of thermoplastic film and the orientation of knitted materials strips in bonded seams upon deformational behaviour of knitted materials bonded seams under uniaxial tension before and after cyclical fatigue loading.…”
Section: Introduction mentioning
confidence: 95%
“…The literature analysis revealed that the bonds quality is usually evaluated applying a uniaxial tension ( Jakubčionienė and Masteikaitė, 2010;Jakubčionienė et al, 2012), a spatial deformation (Busilienė et al, 2015(Busilienė et al, , 2017 or peeling strength tests Daukantienė, 2016, 2017), etc. Important indications of bonds' quality are their strength, elasticity, thickness, stiffness and comfort (Seram and Nandasiri, 2015;Jana, 2011).…”
Section: Ijcst 322mentioning
confidence: 99%